Approaches to Successfully Delivering Rehabilitative Services in Prison: Perspectives from Non-Uniform Correctional Staff in Eight States - Dewey, Susan (The prison journal, 2024)
Non-uniform staff help create prison social climate by providing services that include educational and vocational classes, mental health counseling, employment and reentry preparedness, and family-strengthening activities. The present study examines how non-uniform correctional staff perceive their association with successful delivery of rehabilitative services in correctional settings. After accompanying hundreds of non-uniform prison staff throughout their daily professional routines and conducting interviews with them in institutions supervised by eight different U.S. state prison systems, a threefold typology of approaches to successfully delivering rehabilitative services in prison was identified: holistic, pragmatic, and community-oriented.